If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 1 + 2x = 10 Reorder the terms: 1 + x + 2x = 10 Combine like terms: x + 2x = 3x 1 + 3x = 10 Solving 1 + 3x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 3x = 10 + -1 Combine like terms: 1 + -1 = 0 0 + 3x = 10 + -1 3x = 10 + -1 Combine like terms: 10 + -1 = 9 3x = 9 Divide each side by '3'. x = 3 Simplifying x = 3
| g^2+2g-8=0 | | 2+x(23-7)=40 | | x+(x+2)+(x+4)+(x+6)=136 | | 3=b*3 | | g^2-49g=0 | | 35=-3+5(x+6) | | 9z+35=125 | | 3y-8=28 | | -5x+40=-25+87x | | 190=111-x | | 16-w=175 | | 25=6r+1 | | 4y^3-7y^2-16y+28= | | 35.9x+7.19y=31.595 | | -55x-65=71+6x | | -14=7(-3+n) | | -8(3+n)=32 | | -56=-7(p-7) | | -63x+89=22-63x | | -16=3+n | | 9x^2+3=147 | | 7x^2-105-0=0 | | -2=2v+6 | | -31=-7+4u | | 1.20*400= | | -8+3y=-23 | | 2(x+12)=0 | | (2x-17)=(3x+10) | | -24=4(1+x) | | 26=3w-10 | | 2s-6=4 | | 9w/3 |